Naturally occurring products in cancer therapy - E Rajesh; Leena S Sankari; L Malathi; Jayasri R Krupaa (Wolters Kluwer Medknow Publications, 2015)
Natural products have been used for the treatment of various diseases and are becoming an important research area for drug discovery. These products, especially phytochemicals have been extensively studies and have exhibited anti-carcinogenic activities by interfering with the initiation, development and progression of cancer through the modulation of various mechanisms including cellular proliferation, differentiation, apoptosis, angiogenesis, and metastasis. This concept is gaining attention because it is a cost-effective alternative to cancer treatment. In this article, we have discussed some of the naturally occurring products used in cancer treatment.